Thermal degradation of polytetrafluoroethylene in flowing helium atmosphere II. Product distribution and reaction mechanism - Jun, H.S.; Kim, K.N.; Park, K.Y.; Woo, S.I. (Springer-Verlag, 1995)
The thermal degradation of polytetrafluoroethylene was studied in the helium flowing atmosphere and the temperature range 510-600°C. The products of the thermal degradation of polytetrafluoroethylene were analyzed by an on-line gas Chromatograph and the product distribution was obtained. The products consist of tetrafluoroethylene (TFE), perfluoropropene (PFP) and cyclic-perfluorobutane (c-PFB). Under most conditions the main product was TFE. The c-PFB was regarded as the secondary product formed from TFE because the formation of c-PFB strongly depended upon the degradation rate. However, the production of PFP was not related to the degradation rate, but it was influenced by diffusion limitation of gaseous product in the sample matrix. These phenomena were also verified with Curie-point pyrolyser. The results showed that the production of PFP reached a maximum point under diffusion limitation condition. The degradation mechanism of polytetrafluoroethylene was proposed in terms of unzipping mechanism and other mechanism like radical chain transfer reaction. ？ 1995 Korean Institute of Chemical Engineering.